La seguridad ciudadana, el uso de armas y su incidencia en las garantías constitucionales - Meléndez Vega, Víctor Rodolfo (2015)
The present work of Legal Research, it takes in order to submit a proposal to discuss public safety, the use of weapons and their impact on constitutional guarantees. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research described in point; methods applied types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained by interviewing authorities based Quevedo, in addition to surveys of lawyers in professional outdoor exercise, known as are violated without regard to the rights of the litigants prosecutions ranging causing loss of time and money. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter discusses the proposal, objectives, description of the proposal, beneficiaries and social impact, etc.